Water and Sediment Quality Status of the Enim River, South Sumatra - Resarizki Utami; Arissya Novia Sari; Ahmad Daudsyah Imami; Rifka Noor Azizah; Dion Awfa (Indonesian Journal of Limnology, 2024)
The Enim River in Muara Enim Regency, South Sumatra, remains vital for various community activities. However, as an open water source, it is vulnerable to waste inputs from surrounding human activities, which impact the river's overall condition. This research aims to assess the water and sediment quality of the Enim River by analyzing key parameters such as pH, TSS, Fe, Mn, and temperature. Additionally, it seeks to explore the correlation between Fe and Mn content in both water and sediment and evaluate the quality status of these elements. The methodology involves descriptive analysis, where the measured values are compared against established quality standards. Correlation analysis is used to examine the relationship between Fe and Mn concentrations in water and sediment. Furthermore, the Pollution Index (PI) and Geo-accumulation Index (Igeo) methods are applied to determine the quality status of water and sediment. The findings indicate that the water quality of the Enim River exceeds acceptable standards for TSS, Iron (Fe), and Manganese (Mn). Regarding sediment quality, the Iron (Fe) levels surpass the Severe Effect Level (Level 3), while Manganese (Mn) remains below the Lowest Effect Level (Level 2). The correlation analysis reveals a strong negative correlation (-1) between Fe and Mn in water and sediment, suggesting a tightly linked inverse relationship. Overall, the Enim River's water quality is classified as Mildly to Moderately Polluted. The sediment quality, however, varies. It is categorized as Extraordinarily to Extremely Severely Polluted for Iron (Fe) and Not Polluted for Manganese (Mn).